Straight-through honeycomb ceramic carrier as well as preparation method and application thereof

By using pore-forming agents of multiple reaction temperatures in honeycomb ceramic carriers, the problem of difficulty in heating the three-way catalytic purifier in the cold start stage is solved, and high porosity, low cost and efficient exhaust gas conversion effects are achieved.

CN119638480APending Publication Date: 2025-03-18SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411600205.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing three-way catalytic purifiers are difficult to heat the catalyst quickly during the cold start stage of the automobile, resulting in the exhaust pollutants being discharged without purification and cannot meet the strict exhaust emission standards. At the same time, improving the catalyst performance and contact area will increase costs.

Method used

The straight-through honeycomb ceramic carrier is used, and the blank includes inorganic raw materials, pore-forming agents, binders, lubricants and water. By combining at least three pore-forming agents with different reaction temperatures, it avoids exothermic concentration, reduces sintering difficulty, and improves porosity and compressive strength.

Benefits of technology

It is achieved at low cost to improve the porosity and compressive strength of honeycomb ceramic carriers, enhance their heat transfer capabilities in the cold start stage, reduce cracking caused by uneven temperatures, and improve exhaust gas conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128082190000171
    Figure BDA0005128082190000171
  • Figure BDA0005128082190000181
    Figure BDA0005128082190000181
  • Figure BDA0005128082190000191
    Figure BDA0005128082190000191
Patent Text Reader

Abstract

The invention provides a straight-through type honeycomb ceramic carrier and a preparation method and application thereof, and relates to the technical field of catalytic materials.According to the straight-through type honeycomb ceramic carrier, at least three pore-forming agents are used for a blank, and the glue discharging temperatures of different pore-forming agents are different; through the matching of at least three pore-forming materials with different reaction temperatures, the problems that heat release is concentrated during the reaction of a single pore-forming material, the heat release is easy to quickly release in the sintering process, a large amount of gas is generated, and the green body cracks are solved. According to the preparation method provided by the invention, in the blank sintering procedure, at least three sections of glue discharging are included, the at least three sections of glue discharging are matched with at least three pore-forming agents with different reaction temperatures, and the sintering difficulty of the product is reduced while the high porosity of the product is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic materials, and in particular to a straight-through honeycomb ceramic carrier and a preparation method and application thereof. Background Art

[0002] The three-way catalytic converter (TWC) has been widely used in the world as an effective means of purifying motor vehicle exhaust. However, during the cold start phase of the car, due to the low exhaust temperature, it is difficult to heat the catalyst to the activation temperature in a short time (generally 2 to 3 minutes), resulting in a large amount of exhaust emission pollutants, including carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx) being discharged into the atmosphere without purification, forming the so-called cold start pollution, resulting in the three-way catalytic purification technology being unable to meet the more stringent exhaust emission standards. The use of catalysts with better catalytic performance (such as platinum, palladium, rhodium, etc.) and honeycomb ceramics with larger contact areas will greatly increase costs.

[0003] There are many solutions to the above problems, such as moving the three-way catalytic converter (TWC) as far forward as possible, or even installing it directly at the exhaust manifold outlet to shorten the exhaust path, so that the high-temperature exhaust gas can contact the catalyst more quickly, thereby accelerating ignition. However, this arrangement will cause the three-way catalytic converter to be subjected to severe thermal shock, especially when the engine is running at high load, it will withstand high temperature shocks of up to 1000°C, which will greatly shorten the service life of the three-way catalytic converter.

[0004] Another solution is to add an adsorber in front of the three-way catalytic converter (TWC). The function of the adsorber is to adsorb hydrocarbons in the exhaust gas, which is mainly present in a relatively low temperature state during the cold start phase. The disadvantage of this solution is that the desorption of hydrocarbons has begun at around 250°C, and the three-way catalytic converter still cannot have the best catalytic effect at this temperature. In US5051244A, the three-way catalytic converter is placed behind the zeolite adsorber. The adsorber adsorbs pollutants in the cold start exhaust gas and releases them again as the exhaust system continues to heat up. When the temperature increases and the desorption effect begins to exceed the adsorption effect, the adsorber is short-circuited. The exhaust gas then flows directly through the catalytic purifier. When the operating temperature is reached, a portion of the hot exhaust gas flows through the adsorber until the pollutants are completely desorbed so that they can be effectively converted by the catalytic purifier. However, the above method is technically very complex, expensive and easy to damage.

[0005] In addition to the above two methods, there is also electric heating technology. US5146743A installs an electric heating element outside the three-way catalytic converter to directly heat the catalyst using electric energy to quickly reach the ignition temperature. This method can significantly shorten the ignition time of the catalytic converter, but it consumes a lot of power, which is still a big loss for the battery of the gasoline vehicle.

[0006] Therefore, it is more important to start with the honeycomb ceramic carrier, reduce the heat capacity of the honeycomb ceramic carrier from the root, increase its heat transfer rate, and make it reach the ignition temperature faster. At present, the improvement of the honeycomb ceramic carrier mainly lies in increasing the porosity and reducing the wall thickness, but the above improvements will greatly reduce the compressive strength and other properties of the honeycomb ceramic carrier, making it more fragile. Therefore, it is important to prepare a straight-through honeycomb ceramic carrier with high porosity, fast cold start and high strength.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] One of the objects of the present invention is to provide a straight-through honeycomb ceramic carrier with high porosity, fast cold start and high strength. Its high porosity and narrow pore size distribution enable it to have a uniform pore size distribution while having a low volumetric heat capacity, so that it has a more uniform and stable heat transfer, reduces the cracking phenomenon caused by uneven temperature transfer, and at least solves one of the technical problems existing in the prior art.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned straight-through honeycomb ceramic carrier.

[0010] The third object of the present invention is to provide an application of the above-mentioned straight-through honeycomb ceramic carrier.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] The present invention provides a straight-through honeycomb ceramic carrier, the blank of which comprises: inorganic raw materials, pore-forming agent, binder, lubricant and water;

[0013] There are at least three types of pore-forming agents, and different pore-forming agents have different debinding temperatures.

[0014] The present invention combines at least three pore-forming materials with different reaction temperatures to avoid the problem of concentrated heat release during the reaction of a single pore-forming material, which easily releases heat quickly during the sintering process, generates a large amount of gas, and causes cracking of the green body.

[0015] Typically, at least one pore former debinds at 180°C and at least one pore former does not debind at 180°C.

[0016] Furthermore, the pore-forming agent accounts for 1% to 30% of the total mass of the inorganic raw materials, for example, it can be, but not limited to, 1%, 5%, 10%, 15%, 20%, 25% or 30%; preferably 5% to 30%. When the amount of the pore-forming agent is selected within the preferred range of the present invention, a honeycomb ceramic carrier with a porosity of 55 to 65% can be prepared.

[0017] The binder accounts for 3% to 10% of the total mass of the inorganic raw materials, for example, it can be, but not limited to, 3%, 5%, 8% or 10%;

[0018] The lubricant accounts for 2% to 5% of the total mass of the inorganic raw material, for example, it can be, but not limited to, 2%, 3%, 4% or 5%;

[0019] The water accounts for 40% to 60% of the total mass of the inorganic raw materials, for example, but not limited to 40%, 45%, 50%, 55% or 60%.

[0020] Furthermore, the median particle size D50 of the pore former is between 8 and 40 μm, and the consistency is less than 0.45;

[0021] The consistency of the pore-forming material is controlled to make the pore size distribution of the product narrower and enhance its compressive performance. Its A-axis compressive strength is greater than 2MPa.

[0022] Further, the inorganic raw materials include, by weight, 100%: 20% to 50% of flaky talc, for example, but not limited to 20%, 30%, 40% or 50%; 10% to 30% of flaky raw kaolin, for example, but not limited to 10%, 15%, 20%, 25% or 30%; 15% to 35% of calcined kaolin, for example, but not limited to 15%, 20%, 25%, 30% or 35%; 0% to 10% of silicon oxide, for example, but not limited to 0%, 2%, 5%, 8% or 10%; 10% to 20% of aluminum oxide, for example, but not limited to 10%, 12%, 15%, 18% or 20%.

[0023] Preferably, the inorganic raw materials include 37% to 43% of flaky talc, 10% to 15% of flaky raw kaolin, 30% to 35% of calcined kaolin, 0% to 5% of silicon oxide and 10% to 20% of aluminum oxide, based on 100% by weight. When the amount of each inorganic raw material is selected within the preferred range of the present invention, a honeycomb ceramic carrier with a cordierite content of more than 90% can be produced.

[0024] Preferably, the D50 of the flaky talc is between 5 and 20 μm, for example, it can be, but not limited to 5 μm, 10 μm, 15 μm or 20 μm; the D50 of the flaky raw kaolin is between 5 and 20 μm, for example, it can be, but not limited to 5 μm, 10 μm, 15 μm or 20 μm; the D50 of the calcined kaolin is between 5 and 20 μm, for example, it can be, but not limited to 5 μm, 10 μm, 15 μm or 20 μm; the D50 of silicon oxide is between 1 and 10 μm, for example, it can be, but not limited to 1 μm, 2 μm, 5 μm, 8 μm or 10 μm; the D50 of aluminum oxide is between 1 and 10 μm, for example, it can be, but not limited to 1 μm, 2 μm, 5 μm, 8 μm or 10 μm. The specific D50 limit can ensure that the pore former is slowly debonded under the sintering method of the present invention, effectively reducing the cracking caused by the pore former being debonded too quickly and the problem of excessively large pores caused by the gas escaping too quickly.

[0025] Furthermore, the lubricant includes at least one of alkyl polyether, fatty alcohol polyoxyethylene ether, xanthan gum, potassium laurate and ethylenediaminetetramethylenephosphoric acid.

[0026] Furthermore, the porosity P of the straight-through honeycomb ceramic carrier is greater than 55%, and the A-axis compressive strength is greater than 2Mpa;

[0027] Preferably, the wall thickness of the straight-through honeycomb ceramic substrate is 2 to 6 mils, for example, but not limited to 2 mils, 3 mils, 4 mils, 5 mils or 6 mils;

[0028] Preferably, the pore density of the straight-through honeycomb ceramic substrate is 300 to 1000 cspi, for example, but not limited to 300 cspi, 400 cspi, 500 cspi, 600 cspi, 700 cspi, 800 cspi, 900 cspi or 1000 cspi;

[0029] Preferably, the compartment shape of the straight-through honeycomb ceramic carrier is a quadrilateral or a rectangle;

[0030] Optionally, one or more corners of the quadrilateral or rectangle are rounded;

[0031] Preferably, the straight-through honeycomb ceramic carrier is in the shape of a cylinder, an elliptical cylinder or a racetrack column.

[0032] The present invention also provides a method for preparing the straight-through honeycomb ceramic carrier, comprising: mixing an inorganic raw material, a pore-forming agent, a binder, a lubricant and water to obtain a blank, refining the blank into a plastic clay by vacuum degassing, drying and sintering to obtain the straight-through honeycomb ceramic carrier;

[0033] The sintering process includes three stages of debinding.

[0034] At least three stages of debinding are combined with at least three pore-forming agents with different reaction temperatures to ensure high porosity of the product while reducing the sintering difficulty of the product.

[0035] Among them, the first stage of debinding temperature is 80-180℃, and the heating rate K1 of the process has the following relationship: K1<9-B1*X*Z;

[0036] The second stage of debinding temperature is 180-380℃, and the heating rate K2 of the process has the following relationship: K2<10-B2*X*Z;

[0037] The third stage of debinding temperature is 380-500℃, and the heating rate K3 of the process has the following relationship: K3<15-B3*X*Z;

[0038] Wherein, B1 is the ratio of the heat released by all pore formers to the total heat released at the temperature of the first debonding section;

[0039] B2 is the ratio of the heat released by the incompletely burned pore-forming agent at the second debinding temperature to the total heat released;

[0040] B3 is the ratio of the heat released by the incompletely burned pore-forming agent at the third debonding temperature to the total heat released at the third debonding temperature;

[0041] Wherein, X is the percentage of the pore-forming agent in the total mass of the inorganic raw materials;

[0042] Z is the particle size consistency of the pore-forming agent pyrolyzed in each debinding section. If multiple types of pore-forming agents are decomposed simultaneously in the same debinding section, Z = ∑ (consistency of each pore-forming agent * proportion of each pore-forming agent in the total pore-forming agent mass).

[0043] The heating rate of the three-stage debinding is limited by the heat release, consistency and dosage of the pore-forming agent, and the heat release of the pore-forming agent per unit time is controlled. The combination of the two can prepare a honeycomb ceramic carrier with a porosity higher than 55%. The consistency of the pore-forming material is controlled to make the pore size distribution of the product narrower, enhance its compressive performance, and its A-axis compressive strength is greater than 2MPa.

[0044] Furthermore, the process further includes extruding the plastic clay into a columnar clay through a die of an extruder, cutting the wet green body into a certain length, drying the green body to obtain a dry green body, and then performing a sintering process;

[0045] Preferably, the calcination step is calcining at 1430° C. for 6 to 10 hours, preferably 8 hours.

[0046] In addition, the present invention also provides the use of the above-mentioned straight-through honeycomb ceramic carrier or the straight-through honeycomb ceramic carrier prepared by the above-mentioned preparation method in the exhaust purification of motor vehicles.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The straight-through honeycomb ceramic carrier provided by the present invention uses at least three kinds of pore-forming agents in its blank, and the debinding temperatures of different pore-forming agents are different. By matching at least three pore-forming materials with different reaction temperatures, the problem of concentrated heat release during the reaction of a single pore-forming material, which is easy to release heat quickly during the sintering process, generate a large amount of gas, and cause cracking of the blank is avoided.

[0049] The preparation method provided by the present invention includes at least three stages of debinding in the blank sintering process. The at least three stages of debinding are combined with at least three pore-forming agents with different reaction temperatures, thereby reducing the sintering difficulty of the product while ensuring a high porosity of the product.

[0050] After testing, the straight-through honeycomb ceramic carrier provided by the present invention can improve the conversion efficiency of automobile exhaust gas under the premise of the same catalyst loading amount. After the straight-through honeycomb ceramic carrier is coated with a PGM platinum group catalyst, the loading amount is less than 30.0g / cft, and the emission of the cold start WLTC (Worldwide Harmonized Light Vehicles Test Cycle) cycle test is low, and the NOx release is less than 25mg / km, the CO release is less than 150mg / km, and the THC release is less than 30mg / km. DETAILED DESCRIPTION

[0051] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0053] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0054] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0055] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0056] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0057] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0058] "Z" in this application specification refers to the consistency of the pore-forming agent particles. The test method is to take a small amount of sample and measure it using Malvern Laser Particle Size Analyzer 2000, and the test method is GB / T 19077-2016.

[0059] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0060] Example 1

[0061] 37.2% of flaky talc, 13.4% of flaky raw kaolin, 29.4% of calcined kaolin, 3.6% of silicon oxide and 16.4% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 23% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the total mass of the inorganic raw materials and 45% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0062] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 35%, corn starch accounts for 35%, and SA-33 accounts for 30%.

[0063] After kneading and molding, and then drying at 50°C, the green body is heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 20°C / h in the first debinding process, and then heated to 380°C at a heating rate of 21°C / h in the second debinding process, and then heated to 500°C at a heating rate of 32°C / h in the third debinding process. Then, it is heated to 800°C at a heating rate of 35°C / h, and then to 1300°C at a heating rate of 95°C / h, and finally to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0064] Example 2

[0065] 37.2% of flaky talc, 13.4% of flaky raw kaolin, 29.4% of calcined kaolin, 3.6% of silicon oxide and 16.4% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 23% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 46% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0066] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 35%, corn starch accounts for 35%, and SA-33 accounts for 30%.

[0067] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 21°C / h in the first debinding process, and then heated to 380°C at a heating rate of 23°C / h in the second debinding process, and then heated to 500°C at a heating rate of 36°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0068] Example 3

[0069] 37.2% of flaky talc, 13.4% of flaky raw kaolin, 29.4% of calcined kaolin, 3.6% of silicon oxide and 16.4% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 25% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 48% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0070] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 35%, corn starch accounts for 35%, and SA-33 accounts for 30%.

[0071] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 20°C / h in the first debinding process, and then heated to 380°C at a heating rate of 22°C / h in the second debinding process, and then heated to 500°C at a heating rate of 33°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0072] Example 4

[0073] 40.3% of flaky talc, 10.7% of flaky raw kaolin, 31.9% of calcined kaolin, 2.1% of silicon oxide and 15% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 25% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 48% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0074] The types of the above-mentioned pore formers and their proportions in the pore formers are as follows: PMMA accounts for 32%, potato starch accounts for 36%, and SA-45 accounts for 32%.

[0075] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 20°C / h in the first debinding process, and then heated to 380°C at a heating rate of 22°C / h in the second debinding process, and then heated to 500°C at a heating rate of 34°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0076] Example 5

[0077] 40.3% of flaky talc, 10.7% of flaky raw kaolin, 31.9% of calcined kaolin, 2.1% of silicon oxide and 15% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 28% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 49% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0078] The types of the above-mentioned pore formers and their proportions in the pore formers are as follows: PMMA accounts for 32%, potato starch accounts for 36%, and SA-45 accounts for 32%.

[0079] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 19°C / h in the first debinding process, and then heated to 380°C at a heating rate of 20°C / h in the second debinding process, and then heated to 500°C at a heating rate of 31°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0080] Example 6

[0081] 40.3% of flaky talc, 10.7% of flaky raw kaolin, 31.9% of calcined kaolin, 2.1% of silicon oxide and 15% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 28% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 48% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0082] The types of the above-mentioned pore formers and their mass proportions in the pore formers are: PMMA accounts for 32%, potato starch accounts for 36%, and SA-45 accounts for 32%.

[0083] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 24°C / h in the first debinding process, and then heated to 380°C at a heating rate of 26°C / h in the second debinding process, and then heated to 500°C at a heating rate of 39°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0084] Example 7

[0085] 40.3% of flaky talc, 10.7% of flaky raw kaolin, 31.9% of calcined kaolin, 2.1% of silicon oxide and 15% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 30% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 50% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0086] The types of the above-mentioned pore formers and their mass proportions in the pore formers are: PMMA accounts for 32%, potato starch accounts for 36%, and SA-45 accounts for 32%.

[0087] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 23°C / h in the first debinding process, and then heated to 380°C at a heating rate of 25°C / h in the second debinding process, and then heated to 500°C at a heating rate of 38°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0088] Example 8

[0089] 42.3% of flaky talc, 12.2% of flaky raw kaolin, 33.5% of calcined kaolin, 2% of silicon oxide and 10% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 30% of the total mass of the inorganic raw materials was added to a plowshare mixer for dry mixing for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 50% of water were added for wet mixing for 5 minutes at a rotation speed of 95 rpm.

[0090] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 40%, potato starch accounts for 35%, and SA-18 accounts for 25%.

[0091] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 21°C / h in the first debinding process, and then heated to 380°C at a heating rate of 23°C / h in the second debinding process, and then heated to 500°C at a heating rate of 36°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0092] Example 9

[0093] 42.3% of flaky talc, 12.2% of flaky raw kaolin, 33.5% of calcined kaolin, 2% of silicon oxide and 10% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 35% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 52% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0094] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 40%, potato starch accounts for 35%, and SA-18 accounts for 25%.

[0095] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 26°C / h in the first debinding process, and then heated to 380°C at a heating rate of 28°C / h in the second debinding process, and then heated to 500°C at a heating rate of 42°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0096] Example 10

[0097] 42.3% of flaky talc, 12.2% of flaky raw kaolin, 33.5% of calcined kaolin, 2% of silicon oxide and 10% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 35% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 53% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0098] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 40%, potato starch accounts for 35%, and SA-18 accounts for 25%.

[0099] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 19°C / h in the first debinding process, and then heated to 380°C at a heating rate of 20°C / h in the second debinding process, and then heated to 500°C at a heating rate of 31°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0100] Comparative Example 1

[0101] 37.2% of flaky talc, 13.4% of flaky raw kaolin, 29.4% of calcined kaolin, 3.6% of silicon oxide and 16.4% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 23% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 45% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0102] The types of the above-mentioned pore-forming agents and their proportions in the pore-forming agents are as follows: plastic microspheres account for 35%, corn starch accounts for 35%, and SA-33 accounts for 30%.

[0103] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 18°C / h in the first debinding process, and then heated to 380°C at a heating rate of 20°C / h in the second debinding process, and then heated to 500°C at a heating rate of 30°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0104] Comparative Example 2

[0105] 37.2% of flaky talc, 13.4% of flaky raw kaolin, 29.4% of calcined kaolin, 3.6% of silicon oxide and 16.4% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 25% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 47% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0106] The types of the above-mentioned pore-forming agents and their mass proportions in the pore-forming agents are as follows: plastic microspheres account for 35%, corn starch accounts for 35%, and SA-33 accounts for 30%.

[0107] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 17°C / h in the first debinding process, and then heated to 380°C at a heating rate of 18°C / h in the second debinding process, and then heated to 500°C at a heating rate of 28°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0108] Comparative Example 3

[0109] 40.3% of flaky talc, 10.7% of flaky raw kaolin, 31.9% of calcined kaolin, 2.1% of silicon oxide and 15% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 28% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 48% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0110] The types of the above-mentioned pore formers and their mass proportions in the pore formers are: PMMA accounts for 32%, potato starch accounts for 36%, and SA-45 accounts for 32%.

[0111] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 15°C / h in the first debinding process, and then heated to 380°C at a heating rate of 16°C / h in the second debinding process, and then heated to 500°C at a heating rate of 24°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0112] Comparative Example 4

[0113] 40.3% of flaky talc, 10.7% of flaky raw kaolin, 31.9% of calcined kaolin, 2.1% of silicon oxide and 15% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 30% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 50% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0114] The types of the above-mentioned pore formers and their mass proportions in the pore formers are: PMMA accounts for 32%, potato starch accounts for 36%, and SA-45 accounts for 32%.

[0115] After kneading and molding, it was then dried at 50°C. The green body was heated from room temperature to 180°C at a heating rate of 80°C / h, and then heated to 300°C at a heating rate of 17°C / h in the first debinding process, and then heated to 380°C at a heating rate of 18°C / h in the second debinding process, and then heated to 500°C at a heating rate of 28°C / h in the third debinding process. Then it was heated to 800°C at a heating rate of 35°C / h, and then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, and then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are listed in Table 1.

[0116] Comparative Example 5

[0117] 42.3% of flaky talc, 12.2% of flaky raw kaolin, 33.5% of calcined kaolin, 2% of silicon oxide and 10% of aluminum oxide were used as inorganic raw materials. At the same time, pore-forming agent accounting for 35% of the total mass of the inorganic raw materials was added to a plowshare mixer and dry mixed for 15 minutes at a rotation speed of 95 rpm. After the dry mixing, a lubricant accounting for 5% of the inorganic raw materials and 53% of water were added for wet mixing. The wet mixing time was 5 minutes at a rotation speed of 95 rpm.

[0118] The types of the above-mentioned pore-forming agents and their proportions in the pore-forming agents are as follows: plastic microspheres account for 40%, potato starch accounts for 35%, and SA-18 accounts for 25%.

[0119] After kneading and molding, it is then dried at 50°C. The green body obtained is heated from room temperature to 180°C at a heating rate of 80°C / h, then heated to 300°C at a heating rate of 14°C / h in the first debinding process, then heated to 380°C at a heating rate of 15°C / h in the second debinding process, and then heated to 500°C at a heating rate of 23°C / h in the third debinding process. Then it is heated to 800°C at a heating rate of 35°C / h, then heated to 1300°C at a heating rate of 95°C / h, and finally heated to 1430°C at a heating rate of 50°C / h, and kept warm for 8h, then cooled to obtain the product. The heating rates K1, K2, K3 and their related parameters obtained by the three-stage debinding process are all included in

[0120] In Table 1:

[0121]

[0122]

[0123] The heating rates K1, K2 and K3 of the three stages of debinding are calculated by the relationship:

[0124] (1)K1<9-B1*X*Z

[0125] (2)K2<10-B2*X*Z

[0126] (3)K3<15-B3*X*Z

[0127] Among them, B1, B2, and B3 were calculated by the NETZSCH-STA449C thermal analyzer from Germany.

[0128] The heat of all pore-forming agents in three debinding temperature sections was measured when the temperature was raised from room temperature to 800°C. The thermogravimetry of the sample after the pore-forming agent and the raw material were mixed in proportion was measured. The temperature was raised to 800°C in the same way, and the heat of the three debinding temperature sections was obtained.

[0129] B1 is the ratio of the heat released by all pore formers to the total heat released at the temperature of the first debonding section.

[0130] B2 is the ratio of the heat released by the incompletely burned pore-forming agent at the temperature of the first debinding section to the total heat released at the second debinding temperature.

[0131] B3 is the ratio of the heat released by the incompletely burned pore-forming agent at the temperature of the first and second debonding stages to the total heat released at the third debonding temperature.

[0132] The consistency Z of the pore former is calculated by the LA-960 laser particle size analyzer of HORIBA Company of Japan. There are multiple pore formers in some debinding sections, and Z=∑(consistency of each pore former*proportion of each pore former in the total pore former mass).

[0133] The porosity, compressive strength, catalyst coating amount and other performance indicators of each embodiment are shown in Table 2 below:

[0134]

[0135]

[0136] The porosity test method in the above embodiment is the drainage method, and a sample block of 25*25*25mm±0.5mm is made, and the dry weight of the sample block is weighed; a vacuum pump is used to evacuate for 10 minutes, and then the sample block is boiled in a microwave oven. After being placed at room temperature, excess moisture is blown away by an air gun, and the weight of the sample block is weighed to calculate the water absorption rate.

[0137] The test method for compressive strength is as follows: the sample is made into a sample with a length, width and height of 25mm*25mm*25mm, and is measured using Suzhou Tuobo's universal material testing machine. The test method is the national standard: GB / T4740-1999.

[0138] Test method for catalyst coating amount: Mix ethylene glycol and methanol solution, then add polyethylene glycol, heat to 60°C, stir to dissolve. Add catalyst nanopowder and manganese nitrate in sequence, stir evenly, grind in a high-speed grinder for 30 minutes, add deionized water, and further grind and disperse. Dip-coat the honeycomb ceramic carrier, and test the catalyst coating amount after drying.

[0139] The emissions of NOx, THC and CO are obtained through the WLTC (Worldwide Harmonized Light Vehicles Test Cycle) cycle test, which consists of four parts: low speed section (low589s), medium speed section (medium433s), high speed section (high 455s) and extra high speed section (extra high323s), with a total duration of 1800s.

[0140] A-axis compression: tested using a servo computerized universal material testing machine, using a 25±0.5mm sample block;

[0141] Volumetric heat capacity: The sample is made into a sample with a length, width and height of 10mm*10mm*1mm, and the specific heat capacity tester produced by Brilliance Company is used to measure it.

[0142] It can be seen from Examples 1-2 and Comparative Example 1 in Table 2 that, under the conditions of the same pore-forming agent ratio, pore density and wall thickness, the lower the consistency of the pore-forming agent, the higher the heating rates in the three debinding stages K1, K2 and K3, the higher the compressive strength of the A-axis, the higher the porosity, the lower the NOx, THC and CO emissions, and the smaller the volumetric heat capacity.

[0143] It can be seen from Table 2 that when the consistency of the pore-forming agent is the same, the lower the proportion of the pore-forming agent, the higher the heating rate of the three debinding stages K1, K2, and K3, the higher the compressive strength of the A axis, the higher the porosity, the lower the NOx, THC, and CO emissions, and the smaller the volumetric heat capacity.

[0144] It can be seen from Example 9 and Comparative Example 5 in Table 2 that with the same pore-forming agent ratio, the consistency of the pore-forming material is reduced by 0.3, the heating rate of the K1 debinding section can be increased by 12°C / h, the heating rate of the K2 debinding section can be increased by 13°C / h, the heating rate of the K3 debinding section can be increased by 9°C / h, the porosity is increased by 10%, the A-axis compressive strength is increased by 0.7 MPa, the NOx emissions are reduced by 10 mg / km, the THC emissions are reduced by 8 mg / km, the CO emissions are reduced by 45 mg / km, and the volumetric heat capacity is reduced by 45 (J·℃-1).

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A straight-through honeycomb ceramic carrier, characterized in that: The blank includes: inorganic raw materials, pore-forming agent, binder, lubricant and water; There are at least three types of pore-forming agents, and different pore-forming agents have different debinding temperatures.

2. The straight-through honeycomb ceramic carrier according to claim 1, characterized in that: The pore-forming agent accounts for 1% to 30% of the total mass of the inorganic raw materials, preferably 5% to 30%; The binder accounts for 3% to 10% of the total mass of the inorganic raw materials; The lubricant accounts for 2% to 5% of the total mass of the inorganic raw materials; The water accounts for 40% to 60% of the total mass of the inorganic raw materials.

3. The straight-through honeycomb ceramic carrier according to claim 1, characterized in that: The median particle size D50 of the pore former is between 8 and 40 μm, and the consistency is less than 0.45; Preferably, at least one pore former debinds at 180°C, and at least one pore former does not debind at 180°C; Preferably, the pore-forming agent includes at least three of walnut shell powder, graphite, starch, water-absorbing resin, polymethyl methacrylate and expanded microspheres.

4. The straight-through type honeycomb ceramic carrier according to claim 1, characterized in that: The inorganic raw materials include, by weight, 20% to 50% of flaky talc, 10% to 30% of flaky raw kaolin, 15% to 35% of calcined kaolin, 0% to 10% of silicon oxide and 10% to 20% of aluminum oxide. Preferably, the inorganic raw material comprises, by weight, 37% to 43% of flaky talc, 10% to 15% of flaky raw kaolin, 30% to 35% of calcined kaolin, 0% to 5% of silicon oxide and 10% to 20% of aluminum oxide; Preferably, the D50 of the flaky talc is between 5 and 20 μm, the D50 of the flaky raw kaolin is between 5 and 20 μm, the D50 of the calcined kaolin is between 5 and 20 μm, the D50 of silicon oxide is between 1 and 10 μm, and the D50 of aluminum oxide is between 1 and 10 μm.

5. The straight-through honeycomb ceramic carrier according to claim 1, characterized in that: The lubricant comprises at least one of alkyl polyether, fatty alcohol polyoxyethylene ether, xanthan gum, potassium laurate and ethylenediaminetetramethylenephosphoric acid.

6. The straight-through type honeycomb ceramic carrier according to any one of claims 1 to 5, characterized in that: The porosity P of the straight-through honeycomb ceramic carrier is greater than 55%, and the A-axis compressive strength is greater than 2Mpa; Preferably, the wall thickness of the straight-through honeycomb ceramic carrier is 2 to 6 mil; Preferably, the pore density of the straight-through honeycomb ceramic substrate is 300 to 1000 cspi; Preferably, the compartment shape of the straight-through honeycomb ceramic carrier is a quadrilateral or a rectangle; Optionally, one or more corners of the quadrilateral or rectangle are rounded; Preferably, the straight-through honeycomb ceramic carrier is in the shape of a cylinder, an elliptical cylinder or a racetrack column.

7. The method for preparing the straight-through type honeycomb ceramic carrier according to any one of claims 1 to 6, characterized in that: include: Mixing an inorganic raw material, a pore-forming agent, a binder, a lubricant and water to obtain a blank, refining the blank into a plastic clay by vacuum degassing, drying and sintering to obtain the straight-through honeycomb ceramic carrier; The sintering process includes at least three stages of debinding.

8. The preparation method according to claim 7, characterized in that: The three-stage debinding comprises: The first stage of debinding temperature is 80-180℃, and the heating rate K1 of the process has the following relationship: K1<9-B1*X*Z; The second stage of debinding temperature is 180-380℃, and the heating rate K2 of the process has the following relationship: K2<10-B2*X*Z; The third stage of debinding temperature is 380-500℃, and the heating rate K3 of the process has the following relationship: K3<15-B3*X*Z; Wherein, B1 is the ratio of the heat released by all pore formers to the total heat released at the temperature of the first debonding section; B2 is the ratio of the heat released by the incompletely burned pore-forming agent at the second debinding temperature to the total heat released; B3 is the ratio of the heat released by the incompletely burned pore-forming agent at the third debonding temperature to the total heat released at the third debonding temperature; Wherein, X is the percentage of the pore-forming agent in the total mass of the inorganic raw materials; Z is the particle size consistency of the pore-forming agent pyrolyzed in each debinding section. If multiple types of pore-forming agents are decomposed simultaneously in the same debinding section, Z = ∑ (consistency of each pore-forming agent * proportion of each pore-forming agent in the total pore-forming agent mass).

9. The preparation method according to claim 7, characterized in that: The process also includes extruding the plastic clay into a columnar clay through a die of an extruder, cutting the wet green body into a certain length, drying the green body to obtain a dry green body, and then performing a sintering process; Preferably, the sintering step is to sinter at 1400-1500° C. for 6-10 hours.

10. Use of the straight-through honeycomb ceramic carrier according to any one of claims 1 to 6 or the straight-through honeycomb ceramic carrier prepared by the preparation method according to any one of claims 7 to 9 in exhaust purification of motor vehicles.

Citation Information

Patent Citations

  • Use of a molecular sieve bed to minimize emissions during cold start of internal combustion engines

    US5051244A

  • Process for accelerating the response of an exhaust gas catalyst, and apparatus and electrically heatable carrier bodies for performing the method

    US5146743A